2019
DOI: 10.3892/etm.2019.7378
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 attenuates high glucose‑induced endothelial barrier dysfunction in human umbilical vein endothelial cells by protecting the endothelial glycocalyx

Abstract: Disruption of the endothelial barrier is essential for vascular complications associated with diabetes mellitus, and damage to the endothelial glycocalyx has been demonstrated to participate in this process. Ginsenoside Rg1 (Rg1), the major active component isolated from Panax notoginseng, is widely applied for the protection against vascular injury. The present study aimed to analyze the effect of high glucose on endothelial barrier function and its association with endothelial glycocalyx in human umbilical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Endothelial glycocalyx maintains the vascular function and plays an important role in vascular permeability, leucocyte, platelet adhesion as well as transduction of fluid shearing forces ( 23 , 24 ). FITC-WGA has been shown to bind to the glycoprotein of the glycocalyx ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial glycocalyx maintains the vascular function and plays an important role in vascular permeability, leucocyte, platelet adhesion as well as transduction of fluid shearing forces ( 23 , 24 ). FITC-WGA has been shown to bind to the glycoprotein of the glycocalyx ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rg 1 is the main active ingredient extracted from Panax notoginseng and has been widely used to prevent vascular damage. Recent research ( Zhu et al, 2019 ) showed that high glucoscouldan induce endothelial glycocalyx disorders and increase the expression of heparanase mRNA in HUVEC, and Rg1 treatment can reverse this expression. In addition, after high glucose stimulation, Rg1 treatment can reduce transendothelial resistance and transendothelial albumin pass rate.…”
Section: Protective Effect Of Panax Ginseng Camey On Renal Innate Cellsmentioning
confidence: 99%
“…Several reports have highlighted the following functions of the GCX: mechanotransduction, 123 barrier protection 124 and regulation of permeability, and other functions. Regarding mechanotransduction, due to the transmembrane nature of GCX core proteins, Tarbell and colleagues have noted that the GCX transduces shear and stretch forces into biomolecular responses of ECs.…”
Section: Endothelial Glycocalyx: Its Functions and Implications For Gmentioning
confidence: 99%